2000
DOI: 10.1016/s0142-9612(99)00250-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of calcium phosphate cement particles on osteoblast functions

Abstract: Calcium phosphate cements (CPC) are increasingly used in the orthopedic "eld. This kind of cement has potential applications in bone defect replacements, osteosynthetic screw reinforcements or drug delivery. In vivo studies have demonstrated a good osteointegration of CPC. However, it was also observed that the resorption of CPC could create particles. It is known from orthopedic implant studies that particles can be responsible for the peri-implant osteolysis. Biocompatibility assessment of CPC should then be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 36 publications
8
71
1
5
Order By: Relevance
“…Pioletti et al described that CaP cement particles smaller than 10 mm have an effect on the viability and proliferation of osteoblast-like cells. 40 Evidently, the observed acidity of Calcibon CaP cement in in vitro cell culture experiments does not hamper the final in vivo behavior of the material, because in vivo studies with Calcibon 21,24,41 describe excellent bone compatibility, as characterized by the fast deposition of new bone on the cement surface, which proves that the material is osteoconductive and suitable for clinical purposes. A reason for the excellent in vivo behavior might be vascularization, which provides a continuous flow around the inserted implant that can elute the toxicity of the CaP cement.…”
Section: Discussionmentioning
confidence: 96%
“…Pioletti et al described that CaP cement particles smaller than 10 mm have an effect on the viability and proliferation of osteoblast-like cells. 40 Evidently, the observed acidity of Calcibon CaP cement in in vitro cell culture experiments does not hamper the final in vivo behavior of the material, because in vivo studies with Calcibon 21,24,41 describe excellent bone compatibility, as characterized by the fast deposition of new bone on the cement surface, which proves that the material is osteoconductive and suitable for clinical purposes. A reason for the excellent in vivo behavior might be vascularization, which provides a continuous flow around the inserted implant that can elute the toxicity of the CaP cement.…”
Section: Discussionmentioning
confidence: 96%
“…Titanium (Ti) particles downregulated the gene expression of type I collagen [8], while UHMWPE particles were shown to affect osteoblast differentiation [9]. We showed that particles had a cytotoxic effect [10], modulated the fibronectin gene expression [11], and decreased the adhesion strength [12] of osteoblasts. Moreover, combination of particles and cytokines had a synergic effect on the production of inflammatory factors [13].…”
Section: Introductionmentioning
confidence: 92%
“…3 These particles are generated through years of wear. Any of the materials (metallic, polyethylene, methacrylate, ceramic) used for the implants or even the calcium phosphate cement 4 can be involved. In cases of loose Ti implants, the mean concentration of Ti particles retrieved from tissue surrounding the implants can reach 0.1% of the dry tissue weight.…”
Section: Introductionmentioning
confidence: 99%